2016
DOI: 10.1152/ajplung.00304.2016
|View full text |Cite
|
Sign up to set email alerts
|

B cells in chronic obstructive pulmonary disease: moving to center stage

Abstract: Chronic inflammatory responses in the lungs contribute to the development and progression of chronic obstructive pulmonary disease (COPD). Although research studies focused initially on the contributions of the innate immune system to the pathogenesis of COPD, more recent studies have implicated adaptive immune responses in COPD. In particular, studies have demonstrated increases in B cell counts and increases in the number and size of B cell-rich lymphoid follicles in COPD lungs that correlate directly with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 88 publications
7
93
0
1
Order By: Relevance
“…In addition, B cells, in particular B cell rich lymphoid follicles, are increased in the severe stages of COPD and are most strongly linked with the emphysematous changes in the lung (reviewed in Ref. ). Autoantibodies are also evident in the blood and lung samples from COPD patients .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, B cells, in particular B cell rich lymphoid follicles, are increased in the severe stages of COPD and are most strongly linked with the emphysematous changes in the lung (reviewed in Ref. ). Autoantibodies are also evident in the blood and lung samples from COPD patients .…”
Section: Introductionmentioning
confidence: 99%
“…Lung histological sections, stained with CD45/B220 showed the presence of lymphoid follicles in all cigarette smoke exposed cohorts, but not in air treated animals (S5 and S6 Figs). Lymphoid follicles, consisting of predominantly B lymphocytes, have been characterized in the lungs of patients with severe COPD [40, 41], and independently demonstrated that the chronic cigarette smoke exposure had a profound effect on the mice. Further examination of histological sections revealed airspace enlargement, as measured by mean linear intercept analysis, was greatest in the CS + vehicle and dexamethasone treated mice compared to the MAP3K19 inhibitor treated or air treated mice (Figs 9C and 10, S7 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils provide powerful proteases and are most prominent in acute exacerbations in the lung airways [Tuder 2012]. The role of T and B cells in COPD pathogenesis has growing support from the basic science studies of COPD [Hogg 2004, Seys 2015, Polverino 2016, Morrow 2017. In fact, recent evidence shows a strong correlation between increases in the number and size of B cell-rich lymphoid follicles and COPD severity, as well as a strong correlation between T cell numbers and the amount of alveolar destruction and severity of airflow obstruction [Barnes 2016, Polverino 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent evidence shows a strong correlation between increases in the number and size of B cell-rich lymphoid follicles and COPD severity, as well as a strong correlation between T cell numbers and the amount of alveolar destruction and severity of airflow obstruction [Barnes 2016, Polverino 2016. Finally, B cell products (autoantibodies) were found in COPD blood and lung samples [Polverino 2016].…”
Section: Discussionmentioning
confidence: 99%